Casualty sensitivity in Japan: Information underlying certainty and uncertainty. (September 2019) - Komiya, Yoshitaka
Casualty sensitivity among the general public has long been studied and has obtained robust empirical support. Scholars have assumed that the general public receives confirmed information about the number of casualties in war; however, the public may receive uncertain casualty information. In some cases, they may obtain new information that changes their beliefs. To shed new light on how uncertainty and updating information on casualty numbers affect public attitudes toward the use of force, a two-stage survey experiment with 1657 respondents in Japan was conducted. Findings revealed that initial uncertain information on casualty numbers has a negative impact on public attitudes toward a peacekeeping operation. The two-stage experiment provides empirical evidence that while information updating from certainty to uncertainty on casualty numbers increases public anxiety, the effects of this information updating are not significant. In contrast, information on the number of casualties updating from uncertainty to certainty has a significant impact on public support for troop withdrawal.